Analisis Wacana Kritis Teun A Van Dijk Dalam Film Joko Widodo - Ramnaega Lisfariah Siregar; Syairal Fahmi Dalimunthe; M. Surip (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
Film as an audio-visual communication medium to convey a message to a group of people gathered in a certain place. As a media, many things can be conveyed to the public. One of them is the film